1995
DOI: 10.1017/s002185960007341x
|View full text |Cite
|
Sign up to set email alerts
|

Feeding behaviour, feed intake, chemical and botanical composition of the diet of indigenous goats raised on natural vegetation in a semi-arid region of Zimbabwe

Abstract: SUMMARYThe feeding behaviour of indigenous goats grazing on natural vegetation in a semi-arid region of Zimbabwe was studied over five seasons covering a period of one year (March 1989 to March 1990). The goats were randomly allocated to two groups, A and B, which grazed for 8 h (08.00–16.00 h) and 5 h (11.00–16.00 h) daily, respectively. These grazing times were based on the current practices of smallholder farmers. The botanical and chemical composition of the diet was determined by analysing samples collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 12 publications
2
6
0
Order By: Relevance
“…Our results suggest a limited ability of goats to reduce CT intake rate in the dry season, and we found higher amounts and rates of CT intake during dry season. This was in line with findings of other studies [ 52 , 53 ]. One explanation for this is the loss of leaves among deciduous trees during the dry season.…”
Section: Discussionsupporting
confidence: 94%
“…Our results suggest a limited ability of goats to reduce CT intake rate in the dry season, and we found higher amounts and rates of CT intake during dry season. This was in line with findings of other studies [ 52 , 53 ]. One explanation for this is the loss of leaves among deciduous trees during the dry season.…”
Section: Discussionsupporting
confidence: 94%
“…According to Singh and Oosting [35] if the roughage contains above 65% NDF, it is considered as poor quality feed. Moreover, Norton [33] indicated that the NDF content that ranged from 67% to 78% to be high enough to limit DM intake and digestibility, yet the study by Nyamangara and Ndlovu [36] with goats on natural vegetation with NDF contents of between 59% and 79%, indicates that this cell wall component in the foliage should be adequately degraded. Higher NDF in browse comparing with result of Aster et al [28] 34.14% and Beyene et al [26] 33.29 is attributed in the sampling procedures where fine stems and dry pod were included which have higher lignin contents than leaves and hence high NDF.…”
Section: Chemical Composition and In Vitro Dry Matter Digestibility Omentioning
confidence: 99%
“…Despite the costs involved in searching, recognition and selection of food items in spatially heterogeneous habitats, free-ranging herbivores select food items that maximise energy and nutrient intake (Gross et al 1993, Nyamangara and Ndlovu 1995, Ngwa et al 2000. Also, browsers select plants on the basis of trade-offs between the benefits derived from digestible dry matter as opposed to costs associated with antiherbivory substances such as the phenolics in the browse (McArthur et al 1993).…”
Section: Browse Chemistry and Its Influence On Preferencementioning
confidence: 99%